Cover Picture: Advanced Complex Inorganic Nanomaterials (Eur. J. Inorg. Chem. 13‐14/2016). Issue 13 (6th May 2016) - Ragg, Ruben; Tahir, Muhammad N.; Tremel, Wolfgang
Abstract : The front cover picture shows an active enzyme with a single catalytic center under ambient conditions. Above physiological temperature it denatures, whereas a synthetic nanoparticle containing many catalytic sites is still active. Details are presented in the Microreview by W. Tremel et al. onp. 1906 ff . For more on the story behind the cover research, see theCover Profile .